The Inefficiency of Unemployment: The Supervision Perspective - Calvo, Guillermo A. (Quarterly Journal of Economics, 1985)
We study an example economy with costly labor monitoring under a wage-cum-supervision arrangement, where workers' utilities are not equalized across sectors (workers are identical to each other). Our main task is to look for (and find) a set of "flat" taxes and subsidies that bring about a Pareto improvement over the laissez-faire solution. We show that any of such welfare-improving schemes involves a tax on labor income from those workers whose utility is the lowest.